KOMBINASI TEPUNG DARAH AYAM DAN BEKATUL DENGAN FERMENTOR PUMAKKAL TERHADAP KUALITAS PAKAN AYAM BROILER SEBAGAI SUMBER BELAJAR BIOLOGI - Dhea Ananda; Agus Sutanto; Widya Sartika Sulistiani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2024)
This research aims to (1) find out the effect of the combination of chicken blood meal and rice bran on the quality of broiler chicken feed, (2) find out the best combination of chicken blood meal and rice bran on the quality of broiler chicken feed, and (3) find out that the research results can be used as a source of study in biology. The type of research used is quantitative, using experimental methods and random sampling techniques. This research used a Completely Randomized Design (CRD), applying 4 treatments and 5 repetitions with P1 (10 grams of chicken blood meal, 190 grams of rice bran, 150 ml of pumakkal formula), P2 (15 grams of chicken blood meal, 185 grams of rice bran, 150 ml of pumakkal formula), P3 (20 grams of chicken blood meal, 180 grams of rice bran, 150 ml of pumakkal formula), and P4 (25 grams of chicken blood meal, 175 grams of rice bran, 150 ml of pumakkal). Based on the research results, it can be concluded that there is a real influence of protein content on the quality of the feed combined with chicken blood meal and rice bran, but there is no real influence of fat, water, and crude fiber content. With the best research results, the protein content in P4 = 21.941%, the fat content in P1 = 9.513, the water content in P1 = 14.009%, and the crude fiber content in P1 = 4.949%. The results of this research can be used as biology teaching material in the form of a student worksheet on biotechnology material for high school class XII. The results of the validation of learning resources by material experts, design experts, and language experts concluded that the student worksheet was suitable for use as a learning resource, with an average score of 95% for material experts, 80% for design experts, and 83.3% for language experts.